743. Colonization with Extended-Spectrum Cephalosporin-Resistant Enterobacterales (ESCrE) in Healthcare and Community Settings in Botswana: An Antibiotic Resistance in Communities and Hospitals (ARCH) Study. (4th December 2021) - Mannathoko, Naledi; Mosepele, Mosepele; Gross, Robert; Smith, Rachel; Alby, Kevin; Glaser, Laurel; Richard-Greenblatt, Melissa; Sharma, Aditya; Jaskowiak, Anne; Sewawa, Kgotlaetsile; Cowden, Laura; Reesey, Emily; et al.
Abstract: Background: Although ESCrE are a global challenge, data on ESCrE in low- and middle-income countries are limited. In particular, colonization data are critical for larger antibiotic resistance efforts. We characterized the colonization prevalence of ESCrE in various settings in Botswana. Methods: This study was conducted in 3 hospitals and 6 clinics located in 3 districts in Botswana. In each hospital, we conducted surveillance of adult patients. Adult clinic patients were also randomly selected for participation. Finally, we enrolled community subjects by inviting each enrolled clinic subject to refer up to 3 adults. Each adult clinic or community subject was also allowed to refer their children. All subjects had rectal swabs obtained which were inoculated onto chromogenic media for preliminary identification of ESCrE. Final identification and susceptibility testing were performed using MALDI-TOF MS and VITEK-2, respectively. Genotyping was done for identification of extended-spectrum beta-lactamase (ESBL) genes. Results: Enrollment occurred from 1/15/20-9/4/20 but paused from 4/2/20-5/21/20 due to a countrywide COVID lockdown. Of 5, 088 subjects approached, 2, 469 (49%) participated. Enrollment by subject type was: hospital – 469 (19%); clinic – 959 (39%); community adult – 477 (19%); and community child – 564 (23%). Of 2, 469 subjects, the median (interquartile range) age was 32 years (19-44) and 1, 783 (72%) were female. 759 (31%) subjects were colonized with at least one ESCrE; 130 subjects were colonized with multiple strains. E. coli (n=663) and K. pneumoniae (n=121) were most common. ESCrE colonization prevalence was 43% for hospital subjects, 31% for clinic subjects, 24% for adult community subjects, and 26% for child community subjects (p< 0.001)). ESCrE prevalence varied significantly across regions (Figure 1) and was significantly higher pre-lockdown vs post-lockdown (Figure 2). CTX-M was the most common ESBL gene (Figure 3). Figure 1. ESCrE Colonization - Study Sites Figure 2. ESCrE Colonization - Temporal Trends Figure 3. ESCrE Genotypic Analyses Conclusion: ESCrE colonization was common in both healthcare and community settings in Botswana. Colonization prevalence varies by region and clinical setting and decreased following a countrywide lockdown. These findings provide important clues regarding potential drivers of ESCrE that might serve as targets for intervention. Disclosures: Robert Gross, MD, MSCE, Pfizer (Other Financial or Material Support, Serve on DSMB for drug unrelated to HIV) Ebbing Lautenbach, MD, MPH, MSCE, Merck (Other Financial or Material Support, Member of Data and Safety Monitoring Board (DSMB))